Colour image encryption technique using differential evolution in non‐subsampled contourlet transform domain. Issue 7 (1st July 2018) - Kaur, Manjit; Kumar, Vijay
Abstract : The main challenges of image encryption are robustness against attacks, key space, key sensitivity, and diffusion. To deal with these challenges, a differential evolution‐based image encryption technique is proposed. In the proposed technique, two concepts are utilised to encrypt the images in an efficient manner. The first one is Arnold transform, which is utilised to permute the pixels position of an input image to generate a scrambled image. The second one is differential evolution, which is used to tune the parameters required by a beta chaotic map. Since the beta chaotic map suffers from parameter tuning issue. The entropy of an encrypted image is used as a fitness function. The proposed technique is compared with seven well‐known image encryption techniques over five well‐known images. The experimental results reveal that the proposed technique outperforms the other existing techniques in terms of security and better visual quality.